Is there an impact of temporomandibular disorder and anxiety on the academic performance of dental students? - Haddad MF, Valente VB, Zuim PRJ, Brandini DA, Sampaio VHG, Takamiya AS (ARCHIVES OF HEALTH INVESTIGATION, 2019)
Temporomandibular disorder (TMD) has, as one of the mains symptoms, pain and is often associated with psychological factors. TMDs and anxiety interfere with various daily activities and can influence academic performance. The present study aimed to verify a potential association between the presence of TMD, anxiety, and academic performance in dental students. A population of 195 volunteers (73 men and 122 women) aged between 19 and 27 years underwent an oral examination and was interviewed to register the following parameters: personal details, TMD and anxiety diagnosis and academic performance. The Research Diagnosis Criteria for Temporomandibular Disorders (RDC/TMD) was used to identify the presence of TMD, chronic pain grade (CPG) and chronic pain intensity (CPI) in face, the Spielberger's Trait-State Inventory of Anxiety to identify the state and trait of anxiety and Academic performance consisted by average grade of all college. The population was then divided into an absence or present TMD groups. Group differences were analyzed using the Chi-square test, independent t-tests and Spearman correlation test to carried out the association between TMD, gender, age, CPG, CPI, anxiety and academic performance. The results showed that 37.4% of the students had TMD and the intensity of orofacial pain was classified as grade 1 in 72.6% (n = 53) and grade 2 in 20.55% (n = 15) of them. The majority of students presented moderate trait and anxiety status (60% and 51.7%, respectively). The correlation between anxiety trait and the degree of orofacial pain was significant and positive (p = 0.047). No significant correlation was observed between the state of anxiety and the degree of orofacial pain (p= 0.137). There was no correlation between academic performance and TMD (p = 0.48), chronic orofacial pain (p = 0.5), trait and anxiety state (p = 0.48 and p = 0.16). This study concluded that there was a positive correlation of the chronic pain TMD and the trait of anxiety in dental students. There was no correlation between TMD, anxiety and academic performance. Descritores: Orofacial Pain; Temporomandibular Joint; Anxiety.